Pengaruh Pemberdayaan Karyawan, Kecerdasan Emosional, dan Kepuasan Kerja Karyawan terhadap Komitmen Organisasional pada Plan A di Perusahaan Industri Suku Cadang dan Aksesoris Kendaraan Bermotor Kota Cimahi - Ghina Nur Amalia; Arjuna Rizaldi (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2021)
This study aims to determine the effect of Employee Empowerment, Emotional Intelligence, and Employee Job Satisfaction in Plan A in one of the automotive parts and accessories manufacturing companies in Cimahi City, either partially or simultaneously. Considering that in the activities of industrial companies in this study, employees are required to achieve production targets with a predetermined processing time as an effort to meet company targets in order to achieve company goals. So, it is very necessary to have employee commitment in this research company. Descriptive verification is the method that researchers use. Primary data in this study were obtaind from the results of statements (questionnaires) which were distributed directly to 174 respondents, while secondary data were obtained from employee data in this study. SPSS v.25 software is used in this study to analyze multiple linear regression and to test hypotheses. The results obtained are that there is a partially significant effect of employee empowerment on organizational commitment with a positive direction relationship of 0.523; Emotional Intelligence has a significant effect on partial organizational commitment with a positive direction relationship of 0.627; Then on employee job satisfaction as the third independent variable found the results that have a partially significant effect on organizational commitment with a positive direction relationship of 0.063; Employee Empowerment, Emotional Intelligence, and employee job satisfaction can simultaneously affect organizational commitment. In addition, there are results obtained that this research is in the category of a fairly strong relationship with a positive correlation, so it can be concludeid that if the independent variables of employe empowerment, emotional intelligence, and employee job satisfaction are high, the organizational commitment is also higher.